Two-particle Bose-Einstein correlations in $${ pp }$$ pp collisions at $$\mathbf {\sqrt{s} = 13}$$ s=13 TeV measured with the ATLAS detector at the LHC. (Tufts University. Tisch Library., 2022)
Springer Open.